ANALISIS PERAN NOTARIS TERKAIT LEGALITAS PENDIRIAN BADAN USAHA MILIK DESA DI KECAMATAN SUNGGAL KABUPATEN DELI SERDANG (Studi BUM Desa Mencirim Mandiri di Desa Sei Mencirim dan BUM Desa Annur di Desa Purwodadi) - Rita Deliana Manik; Budiman Ginting; T. Keizeirina Devi A - (Ilmu Hukum Prima (IHP), 2021)
Village-Owned Enterprise (henceforth referred to as BUM Desa) as one of rural development programs is established grounded on Village Regulations (henceforth referred to as Perdes), yet its operating activities such as opening a bank account and registering a taxpayer identification number requires a notarial deed its establishment, and so does Mencirim Mandiri and Annur BUM Desa. This research analyzes the roles of a notary related to legality of establishment of Mencirim Mandiri BUM Desa in Sei Mencirim Village and Annur BUM Desa in Purwodadi Village. This research employs normative juridical method. It uses secondary data supported by primary data collected through library study and interview and analysed by qualitative analysis method. The legal grounds for establishment of BUM Desa are Law No. 6/2014 on Village, Law No. 11/2020 on Job Creation, and Government Regulation No. 11/2021 on BUM Desa. BUM Desa can be established grounded on Perdes and is registered electronically. The legal grounds for a notary are not stipulated in Law No. 11/2020 on Job Creation and Government Regulation No. 11/2021 on BUM Desa in term of establishment of BUM Desa, yet as a public official, a notary plays a role in drawing the deeds of establishment of units of BUM Desa. Mencirim Mandiri and Annur BUM Desa were initially established grounded on Village Regulations. The organizers of BUM Desa encounter obstacles to take legal actions with other parties as they require a notarial deed. A notary actually plays a role concerning the units of BUM Desa, in form of legal entities, in line with Government Regulation No. 11/2021 on BUM Desa. It is suggested that Government socialize the Law on Job Creation related to BUM Des and Government Regulation No. 11/2021 on BUM Desa to relevant parties, so that they, particularly the BUM Desa in Sunggal Subdistrict, will properly implement the prevailing laws and regulations and will not mistake the legal entities of BUM Desa from private legal entities.